Single-cell ligand–receptor profiling reveals an immunotherapy-responsive subtype and prognostic signature in triple-negative breast cancer - Chen, Chuanzhi; Qi, Jiahui; Lin, Weichao; Fu, Chunlan; Jin, Xin (Frontiers in Immunology, 2025)
BackgroundTriple-negative breast cancer (TNBC) is an aggressive form of cancer that lacks specific targeted therapies. Although ligand–receptor (LR) interactions play a crucial role in intercellular communication and contribute to tumor heterogeneity, their molecular details and potential as prognostic or predictive markers in TNBC have not been thoroughly investigated.MethodsWe analyzed single-cell RNA sequencing data to categorize TNBC into 12 subgroups and 10 distinct cell types. From this dataset, we identified LR pairs that exhibited significant intercellular crosstalk and evaluated their prognostic relevance in a METABRIC TNBC cohort (n = 298). Through consensus clustering of these LR pairs, two molecular subtypes were defined. Key LR genes were then selected using Lasso regression and stepwise multivariate analysis to build an LR-based prognostic scoring system (LR.score), which was validated using both the METABRIC and GSE58812 datasets (n = 107). Additionally, we performed siRNA-mediated knockdown of the CXCL9/CXCR3 axis in MDA-MB-231 cells, confirming the knockdown via RT-qPCR and Western blot. The functional impact was assessed through proliferation, colony formation, and wound healing assays.ResultsOne subtype (Clust1) demonstrated strong immune cell infiltration, higher immune scores, and enrichment in pathways such as epithelial–mesenchymal transition, angiogenesis, and KRAS signaling—indicative of a basal-like, immune-active phenotype. Among the LR pairs, the CXCL9–CXCR3 axis was identified as a key factor in immune cell recruitment and anti-tumor responses. Functionally, silencing the CXCL9/CXCR3 axis significantly diminished the proliferation, colony formation, and migratory capabilities of MDA-MB-231 cells. Moreover, a higher LR.score was correlated with poorer overall survival (HR = 1.69, 95% CI = 1.12–2.56, P < 0.05) and reduced response to immune checkpoint inhibitors (ICIs), while patients with lower LR.score showed increased sensitivity to ICIs, particularly in anti–PD-L1 cohorts.ConclusionThe LR.score serves as an independent prognostic factor and a reliable predictor of immunotherapy response in TNBC. Targeting crucial LR interactions, especially the CXCL9–CXCR3 axis, may enhance immunotherapeutic efficacy and refine prognostic evaluations, paving the way for improved treatment strategies in TNBC.